Comparative studies of leaf venation in some species of sapindaceae of Malaysia - Mohd Norfaizal G.,; Noraini T.,; Latiff A.,; Masrom H.,; Salmaniza S.,; Nurshahidah M.R., (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study on the variation of leaf venation pattern was undertaken on 43 taxa belonging to 19 genera of Sapindaceae in Malaysia. Results showed that there were 17 venation patterns observed based on the leaf lamina venation, ultimate marginal and veinlet patterns. A total of 15 taxa showed bi-veinlets, 15 taxa uni-veinlets, eight taxa simple veinlets, three taxa tri-veinlet patterns and two other taxa with no ending veinlets. The presence of idioblast cells on the leaf lamina surfaces, presence and localization of simple trichomes on the leaf veins or on the leaf epidermis are the diagnostic characteristics that can be used in identification of Guioa, Harpullia and Glenneia. Druses observed on the leaves lamina can be very useful for species identification of Filicium decipiens (Wight & Arn.) Thwaites. Combination of variation in the leaf venation and diagnostic characteristics found in this study have taxonomic value especially in species and genus identification and differentiation in Sapindaceae in Malaysia.